Analisis Faktor-Faktor yang Mempengaruhi Kualitas Tidur pada Remaja berskala Biner - Muntomimah, Siti; Syahrul Mubarok (Efektor, 2025)
Poor sleep quality in teenagers can cause negative psychological effects such as poor concentration and irritability, making teenagers feel sad, angry or stressed more than usual. The aim of this research is to identify factors that influence adolescent sleep quality, mainly related to sleep hygiene variables, sleep disorders, physical condition, and use of sleeping pills. The sample used in the research was 884 teenagers, using a cluster random sampling technique spread across several cities in East Java. The data analysis technique used is binary logistic regression to identify factors that influence the sleep quality of teenagers on a binary scale. The results of the research show that the factors that have a significant influence on the quality of sleep in adolescents are sleep hygiene, sleep disorders, physical condition, and partial or simultaneous use of sleeping pills. The model obtained shows that increasing sleep hygiene variables and physical condition increases the chances of good sleep quality. Sleep disorders and the use of sleeping medication show that an increase in these two variables can reduce the chances of good quality sleep. This means that in adolescents, interventions are recommended to focus on improving sleep hygiene, physical condition, reducing sleep disorders, and the use of sleeping medication, which can help improve the quality of sleep in adolescents significantly.